Iamblichus and the mystagogy of the gaze: towards an ontology of the image - Benito Torres, Jorge (Analysis. Journal of Philosophical Research, 2022)
The contemporary philosophy reception of Neoplatonism has opened numerous new ways of thinking, which in their own manner have reached the hard cores of this current. Thusly, whilst hermeneutics have noted the milestone that the Neoplatonic metaphysics of the image is, some other authors consider that the highest exponents of aforesaid metaphysics are heavily influenced by irrationalism. At this very same crossroads is where the exegesis of Iamblichus’ work lays. In De Mysteriis, the notion of image (εἰκὼν) gathers a whole net of concepts, which compose an undoubtedly original cosmos. Taking such notion as a guiding principle, we will investigate the ontology suggested by Iamblichus to contemplate the philosophical task as a certain sort of rational mystagogy. i.e., a philosophical initiation on the mysteries of the divine. Linked to this ontology, we will find an exegesis about the powers of the soul and their understandings. This can be understood without the shadow of a doubt as a particular hermeneutics by itself. Finally, such reading will enable us, firstly, to connect the cardinal points of Iamblichus’ philosophy with the Platonic tradition and, secondly, to display the harsh criticism against the Neoplatonic rationalism.